Analysis of the psychometric properties of Ways of Coping Questionnaire of Stressful Events, applied to parents of children with visual disability - Mayo, María Emma; Real, José Eulogio; Taboada, Eva María; Iglesias Souto, Patricia María; Dosil, Agustín (Anales de Psicología / Annals of Psychology, 2012)
The present study analyzes the psychometric properties of the Spanish version of the questionnaire based on Ways of Coping Checklist (W.C.C.), applied to a sample of 147 parents of children with visual impairment affiliated to the National Organization of Spanish Blind (ONCE) in the Autonomous Community of Galicia. The trustworthiness has been checked and a factorial analysis has been done to evaluate the construct validity. The results let us affirm that the Spanish version of the questionnaire is a reliable instrument to evaluate the different ways of parents facing the varied happenings related visual impairment of their children’s.